PEMBERIAN LIMBAH IKAN DAN PEMULSAAN TERHADAP KUALITAS ALLIN SEBAGAI ANTI BAKTERI UMBI BAWANG PUTIH (Allium sativum) VARIETAS LUMBU PUTIH - Untung Sugiarti; Suprihana Suprihana (Universitas Tribhuwana Tunggadewi, 2015)
Organic fertilizer from fish waste is one alternative applied for plants and mulch to improve soil structure, soil and water uptake capacity, improve the environmental conditions of soil and nutrients. This study aims to determine the effect of fish waste and mulch on the production of Garlic var Lumbu umbu White and allin. A factorial Randomized Block Design with three replications. The first factor is the straw mulch (without and with mulch), the second factor is fish waste Io without, I1 50 kg/ha, I2 : 100 kg/ha I3 : 150 kg/ha. Observations were made on the size of bacteria, heavy wet bulb/dry, dimater tubers. The results showed that the mulch and fish waste affect the levels of allicin through the test of essential onion Streptococcus sp 11.33 mm. Bulbs Dry Weight on the area of 20.77 g/plant